2009
DOI: 10.1111/j.1744-1633.2008.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous cholecystitis: A rare condition with variable presentations

Abstract: Aim:  Patients suffering from xanthogranulomatous cholecystitis have variable clinical presentations. The present study aims to evaluate the clinical presentations of the disease and the various surgical treatment strategies in the management of patients suffering from xanthogranulomatous cholecystitis. Methods:  This is a retrospective study in a university teaching hospital and a tertiary referral centre. The histopathological records of 5016 resected gallbladder specimens from January 1991 to June 2007 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…However, in a review by Guzman-Valdivia, predominantly male patients were reported [4]. In this study, the average age at presentation was 62.3 years, which is similar to other studies [8,11,12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in a review by Guzman-Valdivia, predominantly male patients were reported [4]. In this study, the average age at presentation was 62.3 years, which is similar to other studies [8,11,12].…”
Section: Discussionsupporting
confidence: 88%
“…The inflammatory phenomenon in XGC is hypothesized to be effective through the metaplasia-dysplasia-neoplasia sequence [24,25]. Moreover, in 30 % of gallbladder carcinomas, focal xanthogranulomatous changes have been identified in the gallbladder wall that demonstrates neoplastic invasion [26,27]; therefore, frozen section is recommended [4,8,11,12]. Frozen section was performed in 18 patients, and carcinoma was diagnosed in two cases who received radical cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, XGC is often misdiagnosed as GBCa, leading to unnecessary radical surgical excision. The incidence of XGC was approximately 0.2% in our study, the average age was 55.6 years, which was like that found in other studies (7,12), highlighting that the onset age of XGC was relatively late. Although no clinical symptoms were specific to XGC (1), patients present typical features of chronic or acute cholecystitis, including chronic or acute RUQ pain, jaundice, anorexia, abdominal distension, hyperpyrexia, nausea and vomiting, and RUQ mass, with RUQ pain being the most commonly reported complaint (13).…”
Section: Discussionsupporting
confidence: 90%